Aplikasi Pemasaran Elmart Berbasis Android - Aziziyah, Ismi Anisa; Astutik, Ika ratna Indra; Setiawan, Hamzah (STIKOM Tunas Bangsa Pematangsiantar, 2024)
eLMART sells various types of food and drinks. In the current digital era, many shops have difficulty marketing products that can be sold such as food and drinks. As a result, users who want to go to the store don't know what they will get. The aim of this research is to design an Android-based marketing application using agile development techniques which simplify the application design process. In this research, we use agile methodology to design an Android-based application marketing system that allows users to use this marketing application efficiently. Based on the results of research and testing of the Android-based eLMART marketing application as an online advertising medium at the eLKISI Islamic Boarding School which does not yet have a customer-friendly online information system, and efforts to introduce eLMART more widely. As an online advertising medium, there is an information system in the form of the Android-based eLMART marketing application. This marketing application also provides access to administrators. The administrator is the user who controls the application system. One of them is that administrators can add or change items available in the catalog.